2005
DOI: 10.1063/1.2137896
|View full text |Cite
|
Sign up to set email alerts
|

Double optical tweezers for ultrasensitive force spectroscopy in microsphere Mie scattering

Abstract: We used a double tweezers setup to perform ultrasensitive force spectroscopy and observe the forces due to light scattering in a single isolated particle. We demonstrate how to selectively couple the light to the transverse electric ͑TE͒, transverse magnetic ͑TM͒, or both TE and TM microsphere modes by means of the beam polarization and positioning, and to observe correspondent morphology-dependent resonances ͑MDR͒. The results show how the usually assumed azimuthal symmetry in the horizontal plane no longer h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 20 publications
1
18
1
Order By: Relevance
“…For MDR, Fig. 3 it can be observed that each beam polarization excited each mode, TM or TE, separately as has been demonstrated previously [6]. This can be intuitively understood by noticing that only the radial component of the electric field will excite the TM mode, and only the radial component of the magnetic field will excite the TE modes.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…For MDR, Fig. 3 it can be observed that each beam polarization excited each mode, TM or TE, separately as has been demonstrated previously [6]. This can be intuitively understood by noticing that only the radial component of the electric field will excite the TM mode, and only the radial component of the magnetic field will excite the TE modes.…”
Section: Resultsmentioning
confidence: 64%
“…We have shown that a double optical tweezers can be used to perform an ultrasensitive force spectroscopy by observing forces due to the light scattering and selectively coupling the light to either the TE, the TM or both TE and TM microsphere modes in a single isolated particle as function of the beam polarization and position [6,7]. Our results showed how careful one has to be when using optical force models for mechanical properties measurements.…”
Section: Introductionmentioning
confidence: 98%
“…Polarization effects might be relevant, on the other hand, when the sphere is at a distance from the axis larger than or of the order of the radius [35]. They will be discussed in a forthcoming work.…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence for the resonance force enhancement has been obtained in waveguide couplers 35 and in the case of off-axially shifted focused beams. 36 More recently, the notable advance in this field has been made based on theoretical demonstration of high peak-to-background resonant force ratios in evanescent prism couplers. 37,38 However, many properties of resonant light forces still await a thorough investigation.…”
Section: Introductionmentioning
confidence: 99%